Proposed upgrading of Darul Ridzuan Museum for Lembaga Muzium Negeri Perak at Jalan Panglima Bukit Gantang Wahab, 30000 Ipoh, Perak / Adilla Othman - Othman, Adilla (Faculty of Architecture, Planning and Surveying, 2010)
The final project for the student of Diploma in Interior Design is a manifestation towards the student's knowledge about the whole aspect on interior design that had been learnt from basic to the final presentation on the proposed design. The project that had been chosen for the final project is to Propose Upgrading of Darul Ridzuan Museum which is situated at Jalan Panglima Bukit Gantang Wahab, 30000 Ipoh, Perak Darul Ridzuan. This museum's function is to propagate knowledge about history and culture of Perak to the general public especially the younger generation, to strengthen the role of museums in the formation of the nation in the era of globalization and the explosion of information technology and to promote and strengthen cooperation in the integration of research work, marketing and development with other institutions-institution in and outside the country. The target visitors for this museum are public and foreigner and because of that, this museum should be always comes with new environment and look so that can bring comfort to the visitors. Concept and image that had been chosen not only must he suitable with the clients as both of it would reflect the client itself, but at the same time it would give a positive impact and to increase the faith in the customers and the workers in Darul Ridzuan Museum. Connected to that, the chosen design style for Darul Ridzuan Museum is based on modern classical design, goes all the way with the client's needs as they want the museum to have the modem image and at the same time would remain the certain classical elements so that can attract the customers with different image that they would only get in Darul Ridzuan Museum. Before getting a desired design that is suitable with the client's needs, some data analysis should be done where these analysis is on types of customers to attend the session, types of services, spaces to be concluded in the proposed area, operation time and information about other museum that use the same system in management. Some of the gained information of the study is through interviews, printed media, internet, observation, and through the result from the case study either locally or internationally.